Effect of commercial inoculants on fermentation of 1987 silage crops - K. Bolsen; A. Laytimi; R. Hart; L. Nuzback; F. Niroomand; L. Leipold; H Ilg (Kansas Agricultural Experiment Station Research Reports, 1988)
Fourteen commercial silage inoculants were evaluated in 32 trials using nine different crop species harvested in 1987 and ensiled in PVC laboratory silos. Microorganism profiles of the crops showed high numbers of lactic acid bacteria (LAB) in all but one trial. Most inoculants supplied relatively high numbers of LAB per gram of crop–52 of the 66 inoculant samples supplied more than 10 (100,000) viable LAB per gram. The forage crops–wheat, bromegrass, sudangrass, and alfalfa–were highly responsive to the inoculants. When compared to untreated silages, treated silages had lower pH, acetic acid, ethanol, and ammonia-nitrogen values and higher lactic acid content. In general, late summer- and early autumn- harvested row crops–corn, grain sorghum, forage sorghum, and high moisture shelled corn–ensiled rapidly, and most inoculants had limited effect on the rate and efficiency of fermentation.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Inoculants; Fermentation; Silage crops